Vanadium uptake, translocation and bioaccumulation in ecosystem of Skadar Lake, Montenegro - Slađana Krivokapić; Dijana Đurović (Zaštita Materijala)
Lake Skadar is a highly vulnerable ecosystem affected by various types of anthropogenic pressures. In the last few years, interest in vanadium (V) has increased due to several negative effects on the environment. Our research aims to find the V content per fractions of sediments, and estimate bioavailability, including by analyzing content ratios in the sediment, in water and macrophytes and plant tissue distribution. Low content of vanadium was recorded in the water. In the sediment of Skadar Lake, values were found in the range of 18.1 to 49.5 mgkg-1. The largest amounts of V (11.8 mgkg-1) are found in mineral crystalline lattices (residual fraction), so V is substantially immobilized in the sediment of the lake. Based on the calculated geochemical parameters, it can be concluded that the sediment of Skadar Lake is not contaminated with V and it is under the low risk category at all investigated locations. In the tissues of the examined macrophytes, the mean value of V content, in relation to the location and sampling time, is in the range 0.05-8.15 mgkg-1 of the dry part of the plant. The studied macrophytes showed a low bioaccumulation capacity for V. A different seasonal trend of concentration of V in macrophytes was recorded. And the translocation ability between individual parts of the plant is different and depends on the type of macrophytes.